Study protocol for a randomized controlled effectiveness trial of THRIVE group and peer coaching to promote suicide recovery in crisis stabilization centers - Jennifer D. Lockman; Anthony R. Pisani; M. Alexis Kirk; Kimberly A. Van Orden; Ian J. Cero; Margaret E. Balfour; Kristina Mossgraber; David Jacobowitz; Kenneth R. Conner (Contemporary Clinical Trials Communications, 2025)
Crisis Stabilization Centers (CSCs) offer a person-centered, community-based alternative to Emergency Departments for suicide prevention. CSCs may facilitate the expansion of the 988 Suicide Prevention Lifeline by providing callers with places to go in communities to receive treatment. However, new, recovery-focused psychological interventions for suicide prevention that can be rapidly implemented in CSCs are needed to be effective. This pilot study examines the feasibility, acceptability, and target engagement of the Toward Recovery, Hope, Interpersonal Connection, Values, and Engagement (i.e., THRIVE) for CSCs. THRIVE includes a psychotherapy group and peer-led recovery coaching calls after discharge. This project consists of three phases to adapt, pilot, and test THRIVE in CSCs in preparation for a full-scale effectiveness trial. In phase I, we will use the Model for Implementation Design and Impact (i.e., MADI) to adapt THRIVE to CSCs’ implementation needs (n = 25). In phase II, we will assess the feasibility and acceptability of THRIVE through CSC Stakeholder feedback and completing a pilot trial of THRIVE with CSC guests (n = 20). In phase III, we will complete a pilot randomized effectiveness trial of THRIVE (n = 162) to test the effectiveness of THRIVE on treatment initiation. We will also examine target engagement (i.e., as thwarted belongingness, and perceived burdensomeness) of the THRIVE intervention. Participants will be randomized to (a) Thrive + Discharge & Safety Planning as Usual (i.e., Intervention Arm): or (b) Discharge & Safety Planning as Usual (i.e., Control Arm). Participants complete assessments at baseline, discharge, 1 month, and 3 months. This protocol demonstrates strategies for involving community-based practice partners in research and is the first randomized controlled trial in a CSC sponsored by the National Institute of Mental Health (NIMH).